Large Band Gap in a Quantum Spin Hall Insulator with Weak Spin–Orbit Coupling. Issue 8 (16th May 2018) - Wu, Zhigang
Abstract : The typical quantum spin Hall (QSH) insulator acquires its band gap through spin–orbit coupling (SOC). However, the intrinsic SOC in most materials is rather weak and creates small band gaps comparable to k B T . Here, we present a method to open a giant band gap (>1 eV) in a QSH phase with a weak SOC, employing the tight‐binding (TB) Kane–Mele model for the QSH insulator with the additional feature of periodic defects. By tuning the periodicity of structural defects, one can induce the intervalley scattering to open a large band gap, and we show that the characteristic metallic edge modes of a QSH phase persist even with the inclusion of such periodic defects. Our TB calculations show the existence of a Z 2 odd QSH phase in a Kane–Mele model modified to include periodic defects, demonstrating the coexistence of a giant band gap and the QSH effect with weak SOC. Abstract : By tuning the periodicity of structural defects on graphene, one can induce the intervalley scattering to open a large band gap, and the characteristic metallic edge modes of a quantum spin Hall (QSH) phase persist even with the inclusion of such periodic defects. Thus a large band gap can exist in a QSH insulator with a weak spin–orbit coupling.